1991
DOI: 10.1161/01.hyp.18.1.32
|View full text |Cite
|
Sign up to set email alerts
|

Human astrocytes contain two distinct angiotensin receptor subtypes.

Abstract: The ability of angiotensin peptides to stimulate prostaglandin release and raise intracellular calcium levels by activating a phosphoinositide-specific phospholipase C was assessed in three human astrocytoma cell lines (CRTG3, STTG1, and VVITG2). The addition of angiotensin II to CRTG3 cells resulted in a dose-dependent release of prostaglandin E, and prostacyclin, the production of inositol 1,4,5-trisphosphate, and the mobilization of intracellular calcium. Angiotensin-(l-7), previously considered to be an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
2

Year Published

1991
1991
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(27 citation statements)
references
References 44 publications
3
22
2
Order By: Relevance
“…22 Among the in vitro assays, a presynaptic modulation by AT, receptors of norepinephrine release elicited by field stimulation was found in superfused slices of rat interscapular fat 23 and in atria isolated from guinea pigs. 24 Despite the fact that, as reported for Ang II, Ang-(1-7) is devoid of dipsogenic, pressor, or direct myotropic effects in rats and humans, 910 the observation that it is as potent as Ang II in increasing the release of norepinephrine caused by nerve stimulation of the rat atria (present results) is coincident with the findings that the heptapeptide is as potent as Ang II in releasing vasopressin from the rat hypothalamo-neurohypophysial system, 7 producing neuronal excitation in rat paraventricular neurons, 5 ' 6 eliciting cardiovascular effects injected into the dorsal medulla of rats, 8 and stimulating prostaglandin release from rabbit vas deferens 11 and Q glioma cells, 25 human astrocytes, 26 and porcine aortic endothelial cells. 27 Nevertheless, our results do not agree with those reported by Trachte et al, 11 who found that the noradrenergic neurogenic contractions of the rabbit vas deferens were potentiated by Ang II but not by the heptapeptide.…”
Section: Discussionsupporting
confidence: 89%
“…22 Among the in vitro assays, a presynaptic modulation by AT, receptors of norepinephrine release elicited by field stimulation was found in superfused slices of rat interscapular fat 23 and in atria isolated from guinea pigs. 24 Despite the fact that, as reported for Ang II, Ang-(1-7) is devoid of dipsogenic, pressor, or direct myotropic effects in rats and humans, 910 the observation that it is as potent as Ang II in increasing the release of norepinephrine caused by nerve stimulation of the rat atria (present results) is coincident with the findings that the heptapeptide is as potent as Ang II in releasing vasopressin from the rat hypothalamo-neurohypophysial system, 7 producing neuronal excitation in rat paraventricular neurons, 5 ' 6 eliciting cardiovascular effects injected into the dorsal medulla of rats, 8 and stimulating prostaglandin release from rabbit vas deferens 11 and Q glioma cells, 25 human astrocytes, 26 and porcine aortic endothelial cells. 27 Nevertheless, our results do not agree with those reported by Trachte et al, 11 who found that the noradrenergic neurogenic contractions of the rabbit vas deferens were potentiated by Ang II but not by the heptapeptide.…”
Section: Discussionsupporting
confidence: 89%
“…9 Functionally, we and others have shown that Ang II activates phospholipase C in glial cells, stimulating the hydrolysis of phosphoinositides 3 and mobilizing intracellular calcium. 10 We also showed that Ang II enhances the release of prostaglandin (PG) E2 and prostacyclin (PGI 2 ) from rat C6 glioma cells 11 and human astrocytes, 10 in agreement with earlier studies. 12 - 13 Furthermore, using the two Ang heptapeptides Ang- (2)(3)(4)(5)(6)(7)(8) and Ang-(l-7), we showed that the increase in PG release can be dissociated from the increase in intracellular calcium by the differential actions of these two peptides.…”
supporting
confidence: 90%
“…12 - 13 Furthermore, using the two Ang heptapeptides Ang- (2)(3)(4)(5)(6)(7)(8) and Ang-(l-7), we showed that the increase in PG release can be dissociated from the increase in intracellular calcium by the differential actions of these two peptides. 10 The two responses (PG release and Ca 2+ mobilization) may be due to the presence of multiple Ang receptor subtypes coupled to different signal transduction pathways or to a single receptor coupled to multiple signal transduction pathways generating different responses.…”
mentioning
confidence: 99%
“…Ang-(1-7) was as potent as Ang II in terms of prostaglandin release but did not activate phospholipase C or mobilize intracellular calcium in human astrocytoma cell lines (56). Evidence for the existence of an Ang-(1-7) receptor linked to phospholipase A 2 was also obtained by Jaiswal et al (6,7,57) in C6 glioma cells, endothelial cells and human astrocytes.…”
Section: Angiotensin-(1-7) Signal Transductionmentioning
confidence: 84%